The Macroeconomic Determinants of Export Performance: Evidence From ASEAN-5 (1998-2023) - Wahyudi, W; Setyowati, Eni (Universitas Muhammadiyah Surakarta, 2025)
Purpose: The purpose of this study is to analyze the impact of macroeconomic variables FDI, GDP, inflation, and real interest rates on export performance in ASEAN-5 developing countries during 1998-2023.Methodology: This study uses panel data regression with secondary data sourced from ASEAN-5 countries over a 26-years period. The model specification is based on the Chow and Hausman test, which determined the Fixed Effects Model (FEM) as the most appropriate model for estimation.Results: The test confirmed that the Fixed Effect Model (FEM) model, the results of this study proved that the FDI variable has a significant effect on exports with a negative effect, then the GDP and Inflation variables each have a positive effect on exports in developing ASEAN-5 countries, and for real interest rates do not have a significant effect on exports.Applications/Originality/Value: This study contributes to the literature by integrating four key macroeconomic indicators FDI, GDP, inflation, and the real interest rate into a single panel model for ASEAN-5 over 1998-2023, offering a broader perspective than prior single-variable or single-country studies. The findings show that export performance is primarily driven by production capacity and price stability, while the real interest rate is not a significant determinant. These results provide important policy implications for strengthening export strategies and managing FDI inflows, and they reinforce the Export-Led Growth framework while opening new discussion on the quality of FDI in ASEAN.